Brand Image Analysis and Sales Promotion on the Purchase Decision of Top Coffee Gula Palm Brand Through Brand Equity - Patiku, Melda Yanti; Rosanti, Novita; Verawaty (Jurnal Economic Resource, 2024)
This study aims to find out and analyze the Influence of Brand Image and Sales Promotion on Purchase Decisions of Top Coffee Palm Sugar Through Brand Equity as an Intervening Variable with a research period of 1 month starting from July to August 2024. The analysis method used is Path Analysis using SmartPLS Software ver 3 2024, the purpose is to describe the actual state of the research object to determine the Brand Image and Sales Promotion of the Purchase Decision of Top Coffee Gula Palm Brand Through Brand Equity as Veriabel Intervening in the Tamalanrea Village Community who consume Top Coffee Gula Palm through the submission of statements in the questionnaire. The results of the study were (1) Brand image has a positive and significant effect on brand equity, (2) Sales promotion has a positive and significant effect on brand equity, (3) Brand image has a positive and significant effect on purchase decisions, (4) Sales promotion has a positive and significant effect on purchase decisions, (5) Brand equity has a positive and significant effect on purchase decisions, (6) Brand image has a positive and significant effect on purchase decisions through brand equity, (7) Sales promotion has a positive and significant effect on purchase decisions through brand equity.